(untitled) (The Review of Diabetic Studies, 2024)
Introduction: The nursing profession in Saudi Arabia is going through a phase of change unseen before due to the vision 2030 healthcare change. Nevertheless, although the sector has been modernized, nurses are still experiencing a lot of professional pressure that is occasioned by the nature of the high-acuity work conditions, the multicultural workforce, and the changing socio-cultural demands. Although these pressures have been investigated in individual studies, there is a need to synthesize them in order to realize the current trends of the stress and effectiveness of the coping styles used in the Kingdom of unique clinical environment. Study Objective: The systematic review’s primary objective is to assess and synthesise the available studies on the psychological well being of nurses working in Saudi Arabia. Methodology: After systematic searching through several electronic databases, such as PubMed, CINAHL, Scopus, and Saudi digital library, peer-reviewed articles published within 2015 and 2025 were located. In accordance with the PRISMA principles, the inclusion criteria of the studies involved the concentration on the topic of registered nurses (both Saudi and expatriate), and the availability of empirical data on stressors and coping outcomes. There were a total of [insert number, e.g., 22] studies, which met the inclusion criteria. The Joanna Briggs Institute (JBI) checklists were used to conduct quality appraisal and data synthesis was done with the help of a thematic approach. Conclusion: Occupational stress is a major problem impacting Saudi nursing workforce and jeopardizing the well-being of nurses and their patients. Although some resilience is offered by religious and problem-focused coping, institutional support is essential. Culturally appropriate wellness and mentorship initiatives designed to meet the needs of new graduates, policy changes, and changes in staffing ratios to sustain the healthcare transformation should be implemented, as recommended by the study in the long-term.